Genetically modified mesodermal-derived cells for bone tissue engineering. - Kofron, M.D (IEEE Engineering in medicine and biology magazine)
Alternatives to autografts and allografts for accelerated healing of skeletal defects. This article discusses the use of cells, isolated from tissues originating from the mesodermal germ layer and genetically modified to express bone morphogenetic protein, for bone tissue engineering applications.